Velocity fields of blood flow in microchannels using a confocal micro-PIV system - Lima, R. (2010)
The in vitro experimental investigations provide an excellent approach to understand complex blood flow phenomena involved at a microscopic level. This paper emphasizes an emerging experimental technique capable to quantify the flow patterns inside microchannels with high spatial and temporal resolution. This technique, known as confocal micro-PIV, consists of a spinning disk confocal microscope, high speed camera and a diode-pumped solid state (DPSS) laser. Velocity profiles of pure water (PW), physiological saline (PS) and in vitro blood were measured in a 100mm glass square and rectangular polydimethysiloxane (PDMS) microchannel. The good agreement obtained between measured and estimated results suggests that this system is a very promising technique to obtain detail information about micro-scale effects in microchannels by using both homogeneous and non-homogeneous fluids such as blood flow.